2021
DOI: 10.3390/molecules26175147
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Activity and Development of Low Pt Content Electrocatalysts for Oxygen Reduction Reaction in Acid Media

Abstract: Platinum is a main catalyst for the electroreduction of oxygen, a reaction of primary importance to the technology of low-temperature fuel cells. Due to the high cost of platinum, there is a need to significantly lower its loadings at interfaces. However, then O2-reduction often proceeds at a less positive potential, and produces higher amounts of undesirable H2O2-intermediate. Hybrid supports, which utilize metal oxides (e.g., CeO2, WO3, Ta2O5, Nb2O5, and ZrO2), stabilize Pt and carbon nanostructures and dimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 139 publications
0
8
0
Order By: Relevance
“…The performed study showed the highest surface area of Cs x H (3 + n) − x PMo 12 − n V n O 40 when the Cs:HPA ratio is in the range of 2.5 to 3.5 [42]. Dsoke et al [26] also revealed an improved ORR catalytic activity of Pt nanoparticles embedded inside insoluble W-based polyoxometalate (POM) salt, which synthesized from a Keggin-type heteropolyacid. Furthermore, enhancement of catalytic performance of the mixtures of Pt and Pt alloys with such types of co-supports was demonstrated [37][38][39][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…The performed study showed the highest surface area of Cs x H (3 + n) − x PMo 12 − n V n O 40 when the Cs:HPA ratio is in the range of 2.5 to 3.5 [42]. Dsoke et al [26] also revealed an improved ORR catalytic activity of Pt nanoparticles embedded inside insoluble W-based polyoxometalate (POM) salt, which synthesized from a Keggin-type heteropolyacid. Furthermore, enhancement of catalytic performance of the mixtures of Pt and Pt alloys with such types of co-supports was demonstrated [37][38][39][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 86%
“…In fact, automotive and stationary fuel cell applications are typically limited to about 1700 h and 10,000 h of operations, respectively, while at least 5000 h and 40,000 h of continuous operation are required [17,18]. Therefore, in recent years, most of the research efforts have been devoted to reducing the cathode Pt loadings, without loss of performance and durability [19][20][21][22][23][24][25][26][27]. The decrease of Pt loading under 0.2 mg cm −2 maintaining the membrane electrode assembly (MEA) performance of 1000 mW cm −2 , together with low relative humidity (RH) operation and the enhancement of MEA lifetime are some of the important targets aimed at by the US Department of Energy (DOE) for 2020.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,17,75 In various cases, the oxide supports with improved electrical conductivity still need to be mixed with carbon to fulfill the electrical conductivity requirements. 95 In addition, the catalytic activity of transition metals and the surface OH species of supports also play an influential role in the transformation of adsorbed species.…”
Section: Principlesmentioning
confidence: 99%
“…With regard to the materials, generally, Pt-based catalysts exhibit remarkable electrocatalytic activity for the ORR [ 8 , 9 , 10 ]; however, they suffer from disadvantages in terms of commercialization, such as high costs and long-term instability [ 11 , 12 , 13 ]. Therefore, alternative materials similar to Pt catalysts, including metal oxides [ 14 , 15 ], metal chalcogenides [ 16 ], and carbon materials [ 17 , 18 ], have been proposed.…”
Section: Introductionmentioning
confidence: 99%